2022
DOI: 10.1007/s00167-022-07168-z
|View full text |Cite
|
Sign up to set email alerts
|

The proximal posterior cartilage of the lateral femoral condyle can be used as a reference for positioning the femoral tunnel in ACL reconstruction

Abstract: Purpose To describe the femoral insertion of the ACL using the posterior proximal cartilage of the lateral femoral condyle as the anatomical reference. Methods Twenty knees were dissected. The X-axis (deep-shallow) and Y-axis (high-low) were determined using the femoral diaphysis and the proximal cartilage of the lateral femoral condyle (point C) as a reference, which were easily identiied by direct visualization through the anteromedial portal. The distances to the center of the anteromedial and posterolatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…However, these landmarks are sometimes difficult to define. 6 , 7 , 8 In addition, the arthroscope only provides a 2-dimensional image; therefore, depth relations may be misleading. Usually, industry-supplied aiming devices (so-called offset devices) are used to place a 2.4-mm central pin into the center of the desired location during surgery.…”
Section: Clinical Backgroundmentioning
confidence: 99%
“…However, these landmarks are sometimes difficult to define. 6 , 7 , 8 In addition, the arthroscope only provides a 2-dimensional image; therefore, depth relations may be misleading. Usually, industry-supplied aiming devices (so-called offset devices) are used to place a 2.4-mm central pin into the center of the desired location during surgery.…”
Section: Clinical Backgroundmentioning
confidence: 99%
“…Some parameters can be used to help the surgeon determine these points, such as arthroscopic visual parameters (e.g., the lateral femoral intercondylar crest, bifurcated wall, distal joint margin, posterior intercondylar sulcus, and anterior horn of the lateral meniscus) 9 or radiographic parameters, such as the quadrants of Bernard et al 1 Another little-used parameter is the relationship between the posterior proximal cartilage of the lateral femoral condyle and the ACL in both the high low and shallow deep planes. 5 An anatomical study published in 2022 3 concluded that due to the similarity among specimens in the height of the ACL on the shallow deep axis in relation to the proximal posterior cartilage of the lateral femoral condyle (point C), this point can be used as an arthroscopic intraoperative parameter to define the position of the femoral tunnel in ACL reconstruction. Point C can also be used on the high low axis but with greater caution and the additional use of secondary parameters because of the anatomical variation observed between the cases studied.…”
Section: Video Transcriptmentioning
confidence: 99%
“…Once the intra-articular footprint is identified and the aiming guide is in place, the extra-articular drill sleeve is placed through the drill guide at the predetermined extra-articular footprint location. 14 A guidewire is passed through the guide across the lateral femur to connect the extra-articular (anterolateral ligament) and intra-articular (ACL) femoral footprints, and its position confirmed at both locations. Before tunnel drilling, care is taken to ensure avoidance of injury to the LCL complex at the lateral epicondyle.…”
Section: Surgical Techniquementioning
confidence: 99%